(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Croton schiedeanus Schltd (N.V.: "almizclillo") is a plant used in traditional medicine as an antihypertensive in Colombia. It contains flavonoid, diterpenoid and fenilbutanoid metabolites that have vasodilatation effects linked to the NO/cGMP pathway. This work aimed to assess the capacity of a 96% EtOH extract to prevent the hypertension induced by nitric oxide (NO) deficiency in rats. The NO synthase inhibitor L-NAME (10 mg/kg/d, i.p) was administered during five weeks to three groups of rats (6-7 animals): C. Schiedeanus (200 mg/kg/d, p.o), enalapril (reference, 10 mg/kg/d, p.o) and vehicle (control: olive oil 1 ml/kg/d, p.o). In addition, the blank group received only vehicle. The arterial blood pressure (BP) and heart rate (HR) were measured daily for six weeks. After sacrificing the animals, the aortic rings were isolated, contraction was triggered with phenylephrine (PE 10-6 M) and relaxant responses were achieved with cumulative concentrations of acetylcholine (ACh, 10-10 - 10-4 M). L-NAME increased the systolic arterial pressure in the control group, attaining mean values of 131 mm Hg at week 5, whereas the C. schiedeanus, enalapril and blank groups maintained blood pressure under 100 mm Hg. The capacity of PE to contract aortic rings was greater in the C. schiedeanus, enalapril and blank groups than in the control group (2157, 2005, 1910 and 1646 mg, respectively). The pEC50 values for ACh were as follows: C. Schiedeanus (6.89) >;enalapril (6.39) >; blank (5.68) >; control (5.09). These results give support to C. Schiedeanus as a natural antihypertensive source.